ANALISA APLIKASI PEMBENAH TANAH ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L.) - Onny Chrisna Pandu Pradana; Siti N Andini; Gut Tianigut; Ferziana Ferziana; Marveldani Marveldani; Septiana Septiana; Akbar H Zaini (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
As a crucial aspect of domestic food security, soybean production in Indonesia depends on imported resources. The productivity of soybeans exhibits variability attributed to diverse factors, including climate change (particularly water availability), seed quality, soil fertility, and pest infestations. Soil conditions characterized by adequate water retention and nutrient availability are conducive to optimal soybean yield. Conversely, suboptimal soil conditions impede nutrient and water absorption, thereby limiting production potential. This research aimed to evaluate the vegetative and generative growth response of soybeans to soil amendments, specifically compost, zeolite, and dolomite. This research was conducted between August and November 2023 at the Seed Teaching Farm, Politeknik Negeri Lampung. The research was arranged in a randomized complete block design, with single-factor treatments applied to experimental units. Each treatment was replicated four times, and each replication consisted of three plant samples. The treatments that were used were control (P0), zeolite application at 5 t/ha (P1), dolomite application at 10 t/ha (P2), and compost application at 15 t/ha (P3). Analysis of variance was conducted, then followed by an HSD test at a significance level of 5% and correlation analysis. The results of this research indicate significant responses of soybean growth and yield to the applied soil amendments and among these, compost soil amendment emerges as the most suitable for enhancing soybean production.